Halal Supply Chains in Malaysia and Pakistan: Ethical Foundations, Challenges, and Strategic Directions - Mujahid Hussain; Khadija Aziz; Fazal Ellahi (Journal of Islamic Economics (JoIE), 2025)
Introduction: The exponential growth of the global halal economy has intensified scholarly interest in halal supply chains (HSCs), particularly within Muslim-majority countries. Despite this expansion, comparative institutional analyses of halal logistics governance remain limited, resulting in an incomplete understanding of how different regulatory models influence Shariah compliance, operational efficiency, and international competitiveness. Addressing this gap, the present study examines the ethical foundations, regulatory structures, and logistical performance of HSCs in Malaysia and Pakistan, two prominent halal markets with contrasting governance frameworks. Research Methods: This study adopts a qualitative comparative case study approach. Data were collected from policy documents, industry reports, and 18 semi-structured interviews with supply chain practitioners, halal logistics operators, and officials from halal certification authorities in both countries. The data were analyzed thematically to identify institutional patterns, governance mechanisms, and ethical dimensions shaping the implementation of halal supply chains. Results: The findings demonstrate that Malaysia’s centralized halal governance model, anchored by a single authoritative certification body, enables standardized certification, stronger traceability, and greater international recognition. In contrast, Pakistan’s fragmented regulatory landscape, characterized by multiple certification bodies and weak coordination, undermines the credibility of certification, logistics integration, and access to global halal markets. Conclusion: This study contributes theoretically by integrating Islamic economic ethics with institutional theory in the context of halal logistics governance. In practice, it proposes a strategic roadmap emphasizing cross-border certification harmonization, enhanced stakeholder coordination, and the integration of ethical accountability into supply chain operations. These findings advance the discourse on halal supply chains and offer policy-relevant insights to strengthen the competitiveness of halal logistics in emerging halal economies.